Exposure of e-waste dismantlers from a formal recycling facility in Spain to inhalable organophosphate and halogenated flame retardants. (May 2022) - Balasch, A.; López, M.; Reche, C.; Viana, M.; Moreno, T.; Eljarrat, E.
Abstract: Concentration levels of 16 organophosphate esters (OPEs) and 18 halogenated flame retardants (HFRs) were measured in airborne fine particulate matter (PM2.5 ) from an e-waste dismantling facility in Catalonia (Spain) to assess their occurrence, profiles and potential health risks. Three different areas from the facility were studied, including an area for cathodic ray-tube (CRT) TV dismantling, a grinding area, and the outdoor background. OPEs and HFRs were detected in all samples, with concentrations between 10.4 and 110 ng/m 3 for OPEs and from 0.72 to 2213 ng/m 3 for HFRs. The compounds with highest concentrations in both working areas were triphenyl phosphate (TPHP) and tris(2-chloroisopropyl) phosphate (TCIPP) for OPEs and decabromodiphenyl ether (BDE-209) for HFRs. Higher concentration levels were found in the CRT area compared to the grinding one, probably due to the lower ventilation and different types of e-waste being processed. OPEs were also detected in the solid e-waste from the facility, highlighting the need to evaluate pollutant levels in e-waste before proceeding to its re-use. Estimated daily intakes via inhalation during workday were calculated, as well as carcinogenic and non-carcinogenic health risks, these being 25 and 50 times lower than threshold risk values in the worst cases, respectively. However, this calculated risk only considers the workday exposure via inhalation, while other routes of exposure (e.g., ingestion, dermal) could bring these values closer to threshold values. Graphical abstract: Image 1 Highlights: HFRs and OPEs detected in airborne PM2.5 from an e-waste dismantling facility. BDE-209 and TPHP were the predominant HFR and OPE compounds, respectively. Human exposure to HFRs and OPEs via PM2.5 inhalation during workday was estimated. Workers exposure to HFRs via inhalation was higher than for general population. Inhalation non-CR and CR risks were 50 and 25 times lower than threshold risk values.